Investigating the mechanism of rough phenotype in a naturally attenuated Brucella strain: insights from whole genome sequencing - Han, Wendong; Wei, Dong; Sun, Zhiping; Qu, Di (Frontiers in Medicine, 2024)
Objective Brucellosis, a significant zoonotic disease, not only impacts animal health but also profoundly influences the host immune responses through gut microbiome. Our research focuses on whole genome sequencing and comparative genomic analysis of these Brucella strains to understand the mechanisms of their virulence changes that may deepen our comprehension of the host immune dysregulation. Methods The Brucella melitensis strain CMCC55210 and its naturally attenuated variant CMCC55210a were used as models. Biochemical identification tests and in vivo experiments in mice verified the characteristics of the strain. To understand the mechanism of attenuation, we then performed de novo sequencing of these two strains. Results We discovered notable genomic differences between the two strains, with a key single nucleotide polymorphism (SNP) mutation in the manB gene potentially altering lipopolysaccharide (LPS) structure and influencing host immunity to the pathogen. This mutation might contribute to the attenuated strain's altered impact on the host's macrophage immune response, overing insights into the mechanisms of immune dysregulation linked to intracellular survival. Furthermore, we explore that manipulating the Type I restriction-modification system in Brucella can significantly impact its genome stability with the DNA damage response, consequently affecting the host's immune system. Conclusion This study not only contributes to understanding the complex relationship between pathogens, and the immune system but also opens avenues for innovative therapeutic interventions in inflammatory diseases driven by microbial and immune dysregulation.